AP Anesthesia Analysis of the Implementation of the Refuse-Derived Fuel (RDF) Pilot Test in Rorotan, North Jakarta, in Advancing National Energy Security: Indonesia - Anesthesia, Annisa Priska; Supriyadi, Imam; Purwantoro, Susilo Adi (PendIPA Journal of Science Education, 2025)
The escalating national energy demand and Indonesia's substantial reliance on fossil fuels underscore the imperative for the development of more sustainable alternative energy sources. Conversely, the magnitude of waste management challenges in DKI Jakarta persists, exerting an additional strain on the operational capacity of the Bantargebang TPST. Refuse Derived Fuel (RDF) is regarded as a strategic solution that can address the need for waste reduction and the provision of alternative energy. The objective of this study is to analyze the implementation of the RDF Plant Rorotan trial in DKI Jakarta using the implementation theory approach of Mazmanian & Sabatier and Allan McConnell's Policy Failure Theory model (2010). The methodological approach employed is descriptive qualitative, with data collection through documentation studies and observation.  The results of the study indicate that RDF Rorotan faces various technical, institutional, and social obstacles. According to the findings of Mazmanian & Sabatier's analysis, the characteristics of the problem, the clarity of policy objectives, coordination between relevant actors, and social environment support proved inadequate for achieving effective implementation. The presence of technical challenges, including elevated moisture content in waste, unpublished RDF quality, the ambiguity of off-takers, and complaints from residents regarding odors and health disturbances, suggests a suboptimal level of implementation readiness. McConnell's analysis corroborates the finding that RDF Rorotan is in a position of precarious success, which has resulted in policy failure in three areas: process, program, and politics. Indicators of early implementation failure include declining operational capacity, community resistance, and weakening policy legitimacy. The study's findings indicate that Rorotan RDF has not adequately fulfilled its designated role as a waste management solution and an energy alternative for national energy security. To optimize the potential of RDF, there is a necessity for improvements in quality standards, strengthened coordination, data transparency, and comprehensive environmental management strategies.